Simulasi Optimasi Sistem Pencahayaan Laboratorium Suhu dan Laboratorium Volume - Fitria Hidayanti (Universitas Indraprasta PGRI Jakarta, 2019)
Temperature Laboratory and Volume Laboratory of Metrology Department located on basement need artificial lighting that meets applicable lighting standard. The purpose of this research is to assess the illuminating base on SNI standard using measurement, data analysis, and Calculux software simulation to get the solution of the fulfilment of SNI standard. Based on the measurement, it showed that the illuminating of temperature laboratory was 338 lux and volume laboratory was 134 lux. The solution to SNI compliance was to using Calculux software simulation and the result obtained by changing the position of the lamps and the wall reflectance rate so that a laboratory lighting recommendation value of 500 lux is reached.